Воспитанник Шао - Разбоев Сергей (Супербоевик, 1994)
10-11кл Экземпляры: К.Х. (20201105) / Инвентарный номер: 33302 / Цена: 6500 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6